A Cr2O3-doped graphene sensor for early diagnosis of liver cirrhosis: a first-principles study. Issue 35 (31st August 2022) - Bhateja, Yuvam; Ghosh, Ritam; Sponer, Jiri; Majumdar, Sanhita; Cassone, Giuseppe
Abstract : Via Density Functional Theory approaches including the U correction, here we suggest that chromium-oxide-doped graphene (Cr2 O3 –graphene) heterostructures can be exploited as sensors of key liver cirrhosis biomarkers, such as limonene. Abstract : Liver cirrhosis is among the leading causes of death worldwide. Because of its asymptomatic evolution, timely diagnosis of liver cirrhosis via non-invasive techniques is currently under investigation. Among the diagnostic methods employing volatile organic compounds directly detectable from breath, sensing of limonene (C10 H16 ) represents one of the most promising strategies for diagnosing alcohol liver diseases, including cirrhosis. In the present work, by means of state-of-the-art Density Functional Theory calculations including the U correction, we present an investigation on the sensing capabilities of a chromium-oxide-doped graphene ( i.e., Cr2 O3 –graphene) structure toward limonene detection. In contrast with other structures such as g -triazobenzol (g-C6 N 6 ) monolayers and germanane, which revealed their usefulness in detecting limonene via physisorption, the proposed Cr2 O3 –graphene heterostructure is capable of undergoing chemisorption upon molecular approaching of limonene over its surface. In fact, a high adsorption energy is recorded (∼−1.6 eV). Besides, a positive Moss–Burstein effect is observed upon adsorption of limomene on the Cr2 O3 –graphene heterostructure, resulting in a net increase of the bandgap (∼50%), along with a sizeable shift of the Fermi level toward the conduction band. These findings pave the way toward the experimental validation of such predictions and the employment of Cr2 O3 –graphene heterostructures as sensors of key liver cirrhosis biomarkers.